Analysis of Vitamin C and Antioxidant Activity of Capsicum frutescens L. and Capsicum annuum L. - St Maryam; Rais Razak; Muzakkir Baits; Ainun Fadhilah Salim (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Vitamin C is a nutrient that the body needs in order to increase its metabolism. This helps the body to create collagen and also act as an antioxidant. This study aims to analyze of vitamin C and the antioxidant activity of Capsicum frutescens L. and Capsicum annuum L. (curly and large chili variety), obtained from the Pinrang Regency, South Sulawesi Province. The study was carried out experimentally using the UV-Vis spectrophotometry method. The measurement of vitamin C was carried out at a wavelength of 265.667 nm while for the antioxidant activity test the maximum wavelength of DPPH was 515.961 nm. Vitamin C levels obtained in Capsicum frutescens L. and Capsicum annuum L. (curly and large chili variety), were 0.926; 0.344 and 0.281 % w/w. For antioxidant activity, the results of Capsicum frutescens L. and Capsicum annuum L. (curly and large chili variety), were 2.202; 2,260; and 2.751 ppm while the comparator vitamin C was 12.360 ppm. These results indicate that Capsicum frutescens L. has higher levels of vitamin C than Capsicum annuum L. (curly and large chili variety), while for the antioxidant activity test, the IC50 value of Capsicum frutescens L. and Capsicum annuum L. (curly and large chili variety) had less antioxidant activity than a comparison vitamin C, which means that they have strong antioxidant activity.